Inclusive Disaster Education for Students with Special Needs in Indonesia: A Case Study at SLB BC Harapan Ibu, Jakarta - Dwiningtias, Hamidah Dwiningtias; Pratama, Munil Rizky; Rohmansyah; Laurensius Puntodewo; Rahman, Fathin Aulia; Taqwa Putra Budi Purnomo Sidi Hiram (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Purpose – This study investigates how inclusive disaster education is implemented for students with special needs in Indonesia, addressing a critical gap where vulnerable groups often lack adequate preparedness. It aims to examine the effectiveness of visual learning strategies and identify challenges in practice.Design/methods/approach – A qualitative case study was conducted at SLB BC Harapan Ibu, Jakarta, involving interviews with teachers and parents, classroom observations, and analysis of educational materials and evacuation drills to explore practical implementation and obstacles faced.Findings – The study found that visual media significantly improved students’ understanding of safety procedures. However, challenges remain, including the lack of official educational modules tailored for special needs contexts, insufficient school infrastructure, and the need for repetitive instruction for students with intellectual disabilities. These insights contribute practical knowledge on how inclusive disaster education can be operationalized in special needs schools.Research implications/limitations – This research is limited to a single school context, which may constrain generalizability. Future studies should explore diverse educational settings and develop standardized disaster preparedness materials to ensure broader, effective implementation of inclusive disaster education.